2018
DOI: 10.1111/srt.12471
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the fluorescence of human skin in young healthy adults

Abstract: The intensity of skin autofluorescence showed differences between genders and among anatomical regions. The 340 nm intensity was 1.4 times higher in the male group in all 3 anatomical regions studied. The highest intensity of skin autofluorescence for the peaks at 340/280 nm and 600/400 nm was found on the forehead, whereas the 390/325 nm band was most intensive on the inner upper arm in both genders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
(85 reference statements)
0
3
2
Order By: Relevance
“…On the contrary, Koetsier et al found a small, non-signi cant gender difference in certain sub-populations within current smokers with women having a higher SAF [12]. Furthermore, the mean value of SAF for the healthy group in our study was 2.56, that in comparison to the results published by Yue et al had better outcomes in the reference values given for the Chinese population [30].…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…On the contrary, Koetsier et al found a small, non-signi cant gender difference in certain sub-populations within current smokers with women having a higher SAF [12]. Furthermore, the mean value of SAF for the healthy group in our study was 2.56, that in comparison to the results published by Yue et al had better outcomes in the reference values given for the Chinese population [30].…”
Section: Discussioncontrasting
confidence: 97%
“…Gender and ethnic factors may have an in uence on SAF. However, their impact has not been as consistently determined as that of ageing [29,30]. In this study SAF was reported higher in men than in women (Table 4).…”
Section: Discussioncontrasting
confidence: 56%
“…These dermoscopic features include large amounts of keratin ( 6 ). Porphyrins present in keratin are the most likely candidate for nUVD detection, since 400-nm wavelength reactivity is typical of the Soret band of porphyrins ( 7 ). On the other hand, pseudo-networks were most frequently non-identifiable by nUVD.…”
Section: Discussionmentioning
confidence: 99%
“…The skin is the largest organ of the human body and exhibits significant variation according to anatomical site. There are limited systematic studies of normal human skin fluorescence, particularly as a function of skin topography . Before applying fluorescence EEM for skin cancer or other disorders, it is important to characterize how cutaneous autofluorescence varies according to regional factors.…”
Section: Introductionmentioning
confidence: 99%